Demographic and spatial impact of the internationalization of migration flows in the city of Barcelona - Domingo I Valls, Andreu; Bayona, Jordi; López Gay, Antonio (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
This article analyses the principal demographic and spatial implications of the internationalization of migration flows and the growth of the foreign national population resident in Barcelona. The acceleration of international migration beginning in the 1990s has brought to an end the population decline that started in the 1970s when low fertility coincided with increased longevity, the end of in migration from the rest of Spain and the out-migration of young people for residential reasons to produce rapid population ageing and a fall in the demographic weight of the city within the metropolitan area as a whole. At the same time, the rise of international migration has brought with it a new role for the city as a filter redistributing the new immigrant population. Finally, the analysis of the concentration and segregation of the main foreign nationalities based on 2001 census data demonstrates that there was already much social and demographic variety in different city districts, shows the emergence of new areas and patterns of spatial settlement by the foreign population, and the complexity of their future evolution.